Analisis Program Surabaya Smart City Dalam Menunjang Tata Kelola Lingkungan Kampung Sehati di Kota Surabaya - Raya Maulana Sabilillah; Rachmawati Novaria; Dida Rahmadanik (Public Service and Governance Journal, 2025)
This study aims to analyze the role of the Surabaya Smart City Program in supporting environmental governance in Kampung Sehati, Surabaya City. The Smart City initiative implemented by the Surabaya City Government is part of an urban governance innovation based on integrated information technology and community participation. Kampung Sehati, as one of the pilot areas, serves as a case study to examine how technological approaches, regulations, and citizen engagement shape participatory, adaptive, and sustainable environmental governance. This research uses a qualitative descriptive method through in-depth interviews, field observations, and document studies. The results show that the Surabaya Smart City Program facilitates environmental management through digital platforms such as e-lingkungan, citizen reporting applications, and active community involvement in data-based decision-making. However, challenges remain regarding citizens' digital literacy, unequal participation, and the sustainability of programs after intervention ends. It can be concluded that this program significantly contributes to environmental governance in Kampung Sehati, especially in fostering collaboration between the government, community, and technology, although further efforts are needed to overcome the existing obstacles.